863 Identification and characterization of an immunodominant SARS-CoV-2-specific CD8 T cell response. (9th November 2020) - Gangaev, Anastasia; Kvistborg, Pia
Abstract : Background: Global efforts are ongoing to develop vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease (COVID-19). While there is accumulating information on antibody responses against SARS-CoV-2, less is known about CD8 T-cell recognized SARS-CoV-2 epitopes and the functional state of SARS-CoV-2-specific CD8 T cells. Methods: We analysed samples from 18 patients with ongoing severe and critical COVID-19 disease for CD8 T-cell recognition of 500 peptide human leukocyte antigen (HLA) class I complexes, restricted by 10 common HLA alleles. In addition we carried out an in-depth characterisation of the functional state of identified SARS-CoV-2-specific CD8 T cell responses based on peptide stimulation assays, ex vivo flow cytometry and transcriptome analysis. Results: Several epitopes derived from the open reading frame 1ab polyprotein (ORF1ab) were identified, including an immunodominant epitope restricted by HLA-A*01:01.The immunodominance was further supported by high T cell receptor (TCR) diversity within the CD8 T cells specific for this epitope. In-depth characterisation the immundominant SARS-CoV-2-specific CD8 T cell response revealed a regulated activation program that maintains CD8 T cell survival while halting their effector function and migratory capacity. Conclusions: The ORF1ab, that was found to be the source of an immunodminant SARS-Cov-2-specific CD8 T cell epitope, is not included in the majority of vaccine candidates in development, which may influence their clinical activity. Furthermore, these data may be a cautious indication that SARS-CoV-2 specific CD8 T cells – unlike CD4 T cells – are less likely to contribute to the immunopathology observed in severely and critically ill COVID-19 patients. Ethics Approval: The samples from both COVID-19 patients were collected in accordance with the Declaration of Helsinki after approval by the institutional review boards. Consent: Each participant signed informed consent.